Synthesis and evaluation of anti-tuberculosis and anti-cancer activities of hydroxynaphthoquinone derivatives - Paengsri W. (2014)
Hydroxy-1,4-naphthoquinone derivatives associated with a variety of side chains have been synthesized from 2-hydroxy-1,4-naphthoquinone 1, butylamine, allylamine and selected aldehydes. Their biologically significant activities, anti-mycobacterium tuberculosis (H37Ra strain), anti-cancer (MCF7-breast cancer and NCI-H187-small cell lung cancer) were studied and reported. It was found that (2E,4E)-1,4-dioxo-1,4-dihydronaphthalen-2-yl-5(benzo[d][1,3]dioxol-5-yl)penta-2,4-dienoate 6 showed significant anti-MCF7 and anti-NCI-H187 activities with IC50 value at 3.84 μg/mL and 2.24 μg/mL and was found non-cytotoxic. In addition, 2-((allylamino)(phenyl)methyl)-3-hydroxynaphthalene-1, 4-dione 2f also showed similar bioactivities to those of compound 6 and it showed anti-TB activity with MIC value 25 μg/mL however it was found to display cytotoxic activity against Vero cells.